Women and Batik Conservation on Muria Slopes: A Study of Female Batik Crafters in Kudus - Sa’diyah, Zaimatus (Salasika, 2018)
The worsening condition of nature calls the critical attention of human beings to look for primary keys to deal with. Struggling with the same issue, the local government of Kudus promotes community-based development programs that concern with introducing environmental conservation and education, besides cultural understanding programs, which emphasizes local community awareness in environmentally friendly tourism hosting and management. The youth community is invited to join workshops and training to enrich the skills in some handy craft production, networking and society management, particularly related to batik. “Komunitas Batik Manjing Werni” (KBMW) is one of the community-based development centers that concerns in promoting a unique batik motif. This article aims to describe the role of female crafters of natural motif batik in batik conservation on Muria slope. The main objective is to identify how these female crafters in KBMW contribute to build public awareness around Muria slope conservation through religious teachings and education. The data in this descriptive-qualitative research were obtained through observation, documentation and interviews with key persons in KBMW, people living around KBMW and Kudus regency tourism office.